Description of dental caries status and enamel defect on children aged 6-10 years in District of North Mamuju: Gambaran status karies gigi dan defek email gigi pada anak usia 6-10 tahun di Kabupaten Mamuju Utara - Nursyamsi Djamaluddin; Ayub Irmadani Anwar; Burhanuddin Pasiga; Fuad Husain Akbar; Rasmidar Samad; Rini Pratiwi; Sarah Eva Chalid (Makassar Dental Journal PDGI Makassar, 2020)
Dental caries and developmental defect enamel (DDE) in children are very important in preventing diseases of the oral cavity. Caries and enamel defect decrease quality of life of the individual and may also adversely affect the child's future. This study aimed to examine dental caries and enamel defect in children aged 6-10 years in North Mamuju. This study used pathfinder pilot survey, the subjects were 235 people aged 6-10 years. Boys aged 6-7 years have higher average dft index than girls 4.89 dan 3.22. Based on category 6-7 years has higher dft index than category 8-10 years 6.45 dan 2.85. The enamel defect for category 6-7 years shows 1 child experienced demarcation enamel opacity and none had diffuse opacity enamel and hypoplasia enamel, while category 8-10 years shows 1 child has diffuse enamel opacity, 4 children experienced demarcation enamel opacity and 2 children have hypoplasia. It was concluded that children aged 6-7 years have average dft index is 3.9 (medium category) and the prevalence of dental caries is 79,57%. While the prevalence of enamel defect is 4.27% which was dominated by the demarcation enamel opacity in North Mamuju, West Sulawesi.